Inclusive educational practices through distance education. Experiences in Cuba - Llopiz Guerra, Karel (2020)
The purpose of this works is to expose the diversity of educational practices offered to people with disabilities, who are in conditions of inclusion in Cuba and the preparation that is organized by organizations and institutions in the distance education modality. The actions that are developed to contribute to the fulfillment of the objectives of the Associations that group people with disabilities are addressed, mainly, are aimed at integrating this population segment to achieve a socially useful life with equal rights and opportunities with a full access to education that contributes to their preparation for adult and independent life.